Solar radiation maps fot Ethiopia - Bayou, Tesfaye; Assefa, Abebayehu (Zede Journal of Ethiopian Engineers and Architects, 2023)
Estimates of solar radiation maps for Ethiopia are prepared from measured solar radiation data of 6 sites and estimates from sunshine hour records of 136 sites. The estimates for the 136 sites are determined from their sunshine hour data using the Angstrom’s linear correlation for the inland regions and that of Schuepp’s for the coastal regions where ext reme high and low daily sunshine occurs frequently. The 136 sites are classified into the three climatic zones defined by the EMS and suitable regression constants assigned to each site to estimate the global solar radiation level. From the maps prepared it could be seen that sizable portion of the Country receives on the average a radiation level of about 5500 wh/m2 day-1, thus signifying the solar power potential i.1 the country.